Psychology and Buddhism : from individual to global community - Dockett, Kathleen H., 1942-; Dudley-Grant, G. Rita, 1951-; Bankart, C. Peter, 1946- (International and cultural psychology series., 2003)
Psychology and Buddhism are each concerned with understanding and transforming human behavior. Moreover, both traditions have relevance that extends beyond the individual to the community and global level. Indeed some Buddhist traditions, such as the Nichiren sect, have devoted their entire mission to the establishment of peace worldwide. This book advances a serious consideration of how the goals and practices of psychology can be informed and enriched by Buddhist traditions that transcend the individual to consider the interconnectedness of all things, and the responsibility we have towards the other. Individualistic and psychotherapeutic applications of Buddhism in psychology are examined, followed by a bold step into the community arena, with consideration given to the intersection between community psychology and Buddhist approaches to empowerment, social change, and prevention. The emerging perspective of individuals and communities, empowered and ready to engage the millennium, ultimately has global implications for the future of humankind. Psychology and Buddhism envisions how future integration and collaboration between psychology and Buddhism have the potential to transform the way human beings understand and interact with one another on a global scale.